PENGARUH KUALITAS PRODUK, HARGA, PROMOSI DAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN TEH KEMASAN SIAP MINUM MEREK TEH PUCUK HARUM DI DALUNG - Ni Kadek Novi Dwiyanti; Ni Made Hartini (Journal Research of Management, 2021)
This research is motivated by the phenomenon of purchasing decisions on packaged tea with the Teh Pucuk Harum brand. This study aims to analyze and prove the effect of product attributes, prices, promotions, and distributions on purchasing decisions. This study uses quantitative methods. The sample technique used is purposive sampling technique. The number of respondents used in this study were 90 respondents. Multiple linear regression analysis using SPSS software version 24. Regression equation obtained: Y = 0.227 + 0.367X1 + 0.303X2 + 0.402X3 + 0.303X4. The results of this study indicate that: First, product quality has a positive effect on purchasing decisions on ready-to-drink packaged tea with the Teh Pucuk Harum brand in Dalung. This is evidenced by tcount greater than ttable (3,178 > 1,988). Second, price has a positive effect on purchasing decisions on ready-todrink packaged tea with the Teh Pucuk Harum brand in Dalung. This is proven by tcount greater than ttable (2,215 > 1,988). Third, promotion has a positive effect on purchasing decisions for ready-to-drink packaged tea with the Teh Pucuk Harum brand in Dalung. This is proven by tcount greater than ttable (3.360 > 1.988). Fourth, the distribution has a positive effect on purchasing decisions on ready-to-drink packaged tea with the brand of Teh Pucuk Harum in Dalung. This is proven by tcount greater than ttable (2,398 > 1,988).